Flow and heat transfer in serpentine channels - Karale, Chaitanya M.; Bhagwat, Sunil S.; Ranade, Vivek V. (Aiche Journal, 2013)
Serpentine channels are often used in microchannel reactors and heat exchangers. These channels offer better mixing, higher heat and mass-transfer coefficients than straight channels. In the present work, flow and heat transfer experiments were carried out with a serpentine channel plate comprising of 10 units (single unit dimensions: 1 x 1.5 mm(2) in cross section, length 46.28 mm, D-h 1.2 mm) in series. Pressure drop and heat-transfer coefficients were experimentally measured. Flow and heat transfer in the experimental set-up were simulated using computational fluid dynamics (CFD) models to understand the mechanisms responsible for performance enhancement. The CFD methodology, thus, developed was applied to understand the effect of various geometrical parameters on heat transfer enhancement. A criterion was defined for evaluation of heat transfer performance (heat transfer per unit pumping power), thus, ensuring due considerations to required pumping power. The effect of geometrical parameters and the corresponding mechanisms contributing for enhancement are discussed briefly. Based on the results, a design map comprising different serpentine channels showing heat transfer enhancement with pumping power was developed for Reynolds number of 200 which will be useful for further work on flow and heat transfer in serpentine channels. (C) 2012 American Institute of Chemical Engineers AIChE J, 59: 1814-1827, 2013
Keywords: computational fluid dynamics; heat transfer; pressure drop; serpentine

Flow in vortex diodes - Pandare, Aditya; Ranade, Vivek V. (Chemical Engineering Research & Design, 2015)
A vortex diode is used as a cavitation device for treatment of industrial waste water and also, as a leaky non-return valve in nuclear applications. It consists of a vortex chamber with an axial and tangential port. When the fluid is injected through the tangential port, a strong vortex flow is set up in the diode chamber. This flow is characterized by phenomena such as vortex transition, precessing vortex core, toroidal recirculation zone, reverse flow core and recirculation zone in the axial port. Although studies have been conducted on the ``confined vortex'' class of flows (and some of them on vortex diodes), none of them provides a collective account of key nuances of the flow in a vortex diode. The flow in the diode differs from other confined-vortex flows on account of the axial-velocity deficit, due to which, direct correlations from other confined vortex flows cannot be applied to the diode. This work attempts to address the aforementioned flow characteristics in the diode using results primarily from CFD simulations. The reported methodology, computational model and results will be useful to gain better understanding of flows in vortex diodes and to optimize designs of vortex diodes for variety of applications. (C) 2015 Published by Elsevier B.V. on behalf of The Institution of Chemical Engineers.
Keywords: CFD; Confined vortex; Diode; Precessing vortex core; Recirculation

Flow, mixing, and heat transfer in fluidic oscillators - Khalde, Chirag M.; Pandit, Ajinkya V.; Sangwai, Jitendra S.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2019)
There is an increasing emphasis on process intensification and development of compact, intensified reactors and separators in recent years. Significant efforts are being made to develop such intensified reactors and separators without any moving parts. Some of the recent research studies have proven that a liquid-liquid extractor based on the Coanda effect and feedback oscillations exhibit excellent mixing and liquid-liquid contacting. These fluidic oscillators can potentially be used for a variety of other multiphase reactions and systems demanding enhanced mixing and heat and mass transfer. In this work, we have computationally investigated flow, mixing, and heat transfer in fluidic oscillators based on the Coanda effect. Available information on flow and mixing in fluidic oscillators was critically reviewed and key gaps in the available knowledge with respect to the design and optimization of fluidic oscillators were identified. Computational flow models were developed to characterize key flow features like unsteady flows, secondary vortices, and internal recirculation over a range of Reynolds number (Re = 90-1538) for three different oscillator designs. Systematic numerical studies were carried out to quantify different flow regimes, oscillations, and the influence of key geometric parameters on flow, mixing, and heat transfer. Simulated results were critically analyzed and are presented in the form of dimensionless numbers. The approach and results presented in this work will provide useful insights and a systematic basis for extending the applications of the Coanda-based feedback oscillatory devices for a wide range of engineering applications.
Keywords: CFD; Coanda effect; fluidic oscillators; heat transfer; mixing